Histopathology and recovery of Nile tilapia after exposure to malathion insecticide used for the control of Aedes aegypti - de Mello, Nicoli Paganoti [UNESP]; Santarossa, Maria A. Da Silva [UNESP]; de Carvalho, Ana C. Coleone [UNESP]; Ramos-Espinoza, Fernando Carlos [UNESP]; Machado, Angela A. [UNESP]; Neto, Joaquim G. Machado [UNESP] (My University, 2021)
Malathion is an organophosphate insectide that can intoxicate tilapia fish besides of causing economic losses in the tilapiculture sector due to mortaliy. Therefore, this study aimed to evaluate histological alterations and the recover of gills, liver and kidney of tilapia after acute exposure to diferent concentrations of malathion. The malathion caused in the gills hyperplasia, lamelar fusion, congestion of the venous sinus and lamelar disarrangement. In the liver was found congestion of the sinusoids, nuclear displacement, steatosis and cordonal disarrangement. In the kidney were observed vacuolization of the renal tubule cells, inflammatory infiltrate and increased Bowman's space. After 30 days, gills, liver and kidney recovered from alterations caused by malathion at concentrations of up to 5.0 mg L-1. There were no significant changes (p> 0.05) in water in concentrations of malathion ranging from 3.0 mg L-1 to 9.0 mg L-1. The malathion cause damage in essential organs of tilapia fish survivor at concentations tested, but these fish are capable of recover after 30 days in water free contaminants and can be maintained in aquaculture farm, without economic losses by mortality.
Histopatologia e recupeção de tilapia-do-Nilo após exposição ao inseticida malathion utilizado no controle de Aedes aegypti
Keywords: aquaculture; aquicultura; environmental toxicology; organofosforado; organophosphorous; Pesticidass; Pesticides; pollutants on fish; poluentes em peixes; toxicologia ambiental